Transformasi Pencatatan Keuangan Melalui Implementasi Odoo POS dan Accounting Berbasis RAD Pada UMKM - Roro Mawar Amalia; Suhendi Suhendi (Bulletin of Computer Science Research, 2026)
This study discusses the integrated implementation of Odoo Point of Sale (POS) and Accounting modules at Tahu Bandung Sari Mawar, a small and medium enterprise (SME) that previously managed financial records manually using notebooks. The main issues identified were unstructured transaction recording, difficulties in retrieving past data, poorly documented expense transactions, and the absence of monthly financial reports. This research employed a qualitative case study approach using the Rapid Application Development (RAD) method adapted for ready-made software implementation. In this study, the construction phase focused on system configuration, workflow adjustment, module integration, and testing instead of software development from scratch. Data were collected through observation, interviews, and documentation. System testing used Black Box Testing and User Acceptance Testing (UAT), while evaluation was conducted through qualitative comparative analysis. Black Box Testing results showed that all 7 testing scenarios were successfully executed. UAT results obtained a score of 42 out of 50 (84%), indicating good user acceptance. The comparative evaluation showed that transaction recording time decreased from approximately 5 minutes to 2 minutes after implementation. In addition, Odoo enabled automatic integration between POS and Accounting modules, more detailed transaction recording, and the generation of financial reports from recorded transactions.